2015
DOI: 10.1186/s12906-015-0616-5
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics, experiences and perceptions of naturopathic and herbal medicine practitioners: results from a national survey in New Zealand

Abstract: BackgroundDespite the popularity of naturopathic and herbal medicine in New Zealand there remains limited data on New Zealand-based naturopathic and herbal medicine practice.In response, this paper reports findings from the first national survey examining the characteristics, perceptions and experiences of New Zealand-based naturopaths and herbal medicine practitioners across multiple domains relating to their role and practice.MethodsAn online survey (covering 6 domains: demographics; practice characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
4
10
0
Order By: Relevance
“…Similar sociodemographic characteristics were found among traditional health practitioners in Ethiopia, South Africa, and Tanzania [10,11,12]. Among complementary medicine practitioners in high-income countries, there was also a preponderance of women, but they were a little younger in age (middle-aged, > 40 years) and had higher levels of education (vocational or higher degree) than the traditional health practitioners in our study in Indonesia and in African countries [14,15,16,17]. Greater levels of education could contribute to better awareness, skills, and sustainability of the traditional health care profession [12].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similar sociodemographic characteristics were found among traditional health practitioners in Ethiopia, South Africa, and Tanzania [10,11,12]. Among complementary medicine practitioners in high-income countries, there was also a preponderance of women, but they were a little younger in age (middle-aged, > 40 years) and had higher levels of education (vocational or higher degree) than the traditional health practitioners in our study in Indonesia and in African countries [14,15,16,17]. Greater levels of education could contribute to better awareness, skills, and sustainability of the traditional health care profession [12].…”
Section: Discussionsupporting
confidence: 58%
“…Larger surveys among complementary practitioners in Australia, Canada, Germany, New Zealand, Singapore, the UK and the USA found sociodemographic characteristics (most practitioners were female [14,15,16,17], middle-aged, > 40 years old [14,15,17], held a vocational or higher education degree [16,17]) and practice characteristics (most practitioners had 10 or more years of practice [18], most worked full-time [17], part-time [14], had 7-24 clients per week [14,18,19], the initial consultation and treatment lasted for 30-120 min [16], and high referral between complementary and alternative medicine (CAM) and orthodox practitioners [16]). Most complementary practitioners used several treatment modalities [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of this sample (89.2%) indicated that they achieve this with 80.6% reported referring to scientific journals, 67.2% attending industry events and 55.9% using internet fora. This is similar to what has been found in Naturopaths and herbal medicine practitioners in New Zealand [37] where sources other than peer reviewed evidence are being used to inform practice. Industry events may be evidence-based but, because of commercial involvement, may be perceived as influenced by an element of conflict of interest and internet discussion groups, unless regulated may be of variable quality.…”
Section: Educational and Professional Profilesupporting
confidence: 59%
“…The age range is also consistent with other research into CAM practitioner profiles [36,37]. There are little research data available on NT specifically, however, according to Granger 2014et al [39], NT is a second career for many practitioners with Gale 2014 [30] asserting that many CAM practitioners consider their career as vocational.…”
Section: Demographicssupporting
confidence: 57%
See 1 more Smart Citation